Leader-follower tracking and simulation for two mobile robots - Tan, Shu Xian (Nanyang Technological University, 2024)
With the use of two different controllers: a Model Predictive (MP) controller and a Proportional-Integral-Derivative (PID) controller, this work attempts to achieve leader-follower formation tracking for two mobile robots. The principal aim of this study is to develop and model leader-follower tracking systems. Then, the effectiveness of the two controllers utilized in resolving formation tracking issues will be compared. To conduct experimental research, the MATLAB software platform is used. The goal of the study is to shed light on the effectiveness and applicability of PID and MPC controllers in attaining reliable and precise formation tracking for mobile robot systems through these trials.